Analysis of fracture resistance and surface characteristics of bioactive ceramic cluster filler and bulk fill fiber-reinforced composites in endodontically treated teeth - Hayati, Maulida; Natsir, Nurhayaty; Trilaksana, Aries Chandra (Brazilian Dental Science, 2026)
Objective: This study aimed to compare the mechanical, surface, and interfacial properties of a bioactive ceramic cluster filler composite (TMR-Z Fill 10) and a fiber-reinforced bulk-fill composite (EverX Posterior) in ETT, with intact teeth serving as controls. Material and Methods: Forty-five extracted maxillary premolars were divided into three groups (n = 15): intact teeth, TMR-Z Fill 10 restorations, and EverX Posterior restorations. Fracture resistance was measured using a universal testing machine. Surface roughness and morphology were analyzed by atomic force microscopy (AFM). Interface gaps and elemental composition were evaluated using scanning electron microscopy and energy-dispersive spectroscopy (SEMEDS). Mineralization profiles were determined with Fourier-transform infrared spectroscopy (FTIR). Data were analyzed using one-way ANOVA and Post-Hoc Tukey HSD (p < 0.05). Results: Fracture resistance of TMR-Z Fill 10 (1760.86 ± 330.31 N) was comparable to intact teeth (1785.84 ± 367.25 N) and significantly higher than EverX Posterior (1491.96 ± 275.91 N; p < 0.05). AFM revealed smoother surfaces on composites than on enamel, with TMR-Z Fill 10 showing greater uniformity. SEM demonstrated narrower gaps in EverX (3.60 ± 0.43 µm) than in TMR-Z Fill 10 (8.40 ± 0.82 µm). EDS confirmed bioactive ion release from both composites, while FTIR indicated fluoride-mediated remineralization in TMR-Z Fill 10 but weaker carbonate stability in EverX. Conclusion: TMR-Z Fill 10 preserved fracture resistance and supported remineralization, whereas EverX Posterior provided superior marginal adaptation. Neither material fully replicated intact teeth, but each exhibited distinct advantages for restoring ETT. KEYWORDS Bioactive composite; Endodontically treated teeth; Fiber-reinforced composite; Fracture resistance; Interface gap